PENGARUH BRAND IMAGE, HARGA, DAN KUALITAS LAYANAN TERHADAP MINAT BELI PRODUK FASHION SECARA ONLINE DI JAKARTA : Studi Pada Situs Belanja Online Zalora - Prisca Dwi Ratna Sari, (2020)
This research is a quantitative research that aims to study, analyze, and prove the influence of brand image, price, and service quality on purchase intention. The population in this study uses female respondents who live in Jakarta area and have shopped fashion products online at Zalora. The sample size is 75 respondents. The technique used in sampling is purposive sampling. This study uses data that has been distributed through questionnaires. Data analysis in this research is using Partial Least Square (PLS) analysis method with the help of SmartPLS 3.2.9 software. The results of this study indicate that (1) brand image has an influence on purchase intention with a path coefficient of 0.574. (2) price has an influence on purchase intention with a path coefficient of 0.558. (3) service quality has no influence on purchase intention with a path coefficient −0.288.